Reason, truth, and self : the postmodern reconditioned - Luntley, Michael, 1953- (Routledge, 1995)
Michael Luntley gives a lively introduction to the debate over postmodernism. Covering the key questions of our age, this book is ideal for students of philosophy or the social sciences.